2020
DOI: 10.3390/molecules25081816
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Standardized Extracts from an Ancient Italian Apple Variety (Mela Rosa dei Monti Sibillini) against Carbon Tetrachloride (CCl4)-Induced Hepatotoxicity in Rats

Abstract: The aim of this research was to examine the effect of the hydroalcoholic extracts from the peel (APE) and pulp (APP) of a traditional apple cultivar from central Italy (Mela Rosa dei Monti Sibillini) on CCl4-induced hepatotoxicity in rats. Phytoconstituents were determined by liquid chromatography–mass spectrometry (LC-MS) analysis showing an abundance of proanthocyanidins and flavonol derivatives together with the presence of annurcoic acid in APE. Wistar rats received APE/APP (30 mg/kg oral administration) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…The histological analysis of liver was carried out according to standard method [24]. Liver tissues were collected from the sacrificed animals after the experimental period.…”
Section: Histological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The histological analysis of liver was carried out according to standard method [24]. Liver tissues were collected from the sacrificed animals after the experimental period.…”
Section: Histological Analysismentioning
confidence: 99%
“…Finally, the tissues were embedded in paraffin at 62 °C and 5 μm thick sections were made by using microtome (HM 325, Thermo Scientific, USA) and attached to the glass slide. Thereafter, the sections were stained with haematoxylin and eosin [24]. The histology of liver was observed under a light microscope with × 40 magnification (Olympus-BX43, Japan).…”
Section: Histological Analysismentioning
confidence: 99%
“…The consumption of the hydroalcoholic extracts of this cultivar has shown protective effects against renal ischemia/reperfusion injury and CCl 4 -induced hepatotoxicity in rats [18,19].…”
Section: Introductionmentioning
confidence: 97%
“…In this regard, the application of natural products appears to be a good approach to decrease the mortality of strokes. Among fruits and vegetables regarded as sources of phytonutrients capable of preventing damage from oxidative stress and inflammation, the apple is considered one of the most important from a nutraceutical standpoint [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently focused on the Mela Rosa dei Monti Sibillini, an ancient apple variety cultivated by Romans in the foothills of the Sibillini Mountains, central Italy, between 400 and 900 m of altitude, and recognizable by its small size, its irregular shape, its shades ranging from pink to purplish red, its intense and aromatic aroma and its sour and sugary flavor [19]. This fruit has been revealed to be rich in polyphenols such as flavan-3-ols/procyanidins, dihydrochalcones, flavonols, and hydroxycinnamic acids, as well as triterpene acids including annurcoic and ursolic acids, being valuable as source of nutraceuticals useful to manage conditions related to inflammation and oxidative stress [16]. As a matter of fact, in several studies apple peel extract (APE) and apple pulp extract (APP) have shown anti-inflammatory and anti-oxidative stress effects in animal models of renal ischemia/reperfusion injury, carbon tetrachloride (CCl4)-induced hepatotoxicity, diabetic pancreas model and colitis via down regulation of NF-kB, pro-inflammatory cytokines, increasing the antioxidant enzyme activity including superoxide dismutase (SOD), catalase (CAT) and reducing myeloperoxidase (MPO) activity [1,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%